Difus\~ao biotecnológica: A adoç\~ao dos transgênicos na agricultura - José Eustáquio Ribeiro Vieira Filho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– The genetic engineering techniques are essential in modern agriculture and, at the same time, demand regulation on several levels. The diffusion of planting genetically modified organisms (GMOs) has grown since 1996, notably in the United States, Argentina and Canada. In Brazil, the production of genetically modified soybeans began illegally and with a slow adoption rate in 1997. The legalization of genetically modified soybean planting in 2003 intensified the spread of biotechnology in Brazil. This study presents two epidemic models of technology diffusion: exponential (central source) and logistic (contagion). The results obtained suggest that the diffusion process is best described by a logistic function. Although the study does not discuss in detail the function's parameters, it is understood that the trajectory of the logistic curve is fairly complex, since there is no equilibrium for fixed values over time.
Keywords: O33; Q16; Q55; 330; diffusion; biotechnology; logistic function; GMO